Current situation, phytosanitary problems and alternatives for teak management in Ecuador - Borja Borja, Edwin José (2021)
Tectona grandis L.f. (teak) is a forest resource with great international demand, which in Ecuador represents an important income that generates approximately 37 million dollars annualy. However, in recent years it has been threatened by a phytosanitary problem called “dieback disease”. In order to determine the profile of teak producers and the disease incidence, information was collected through a semi-structured survey in 77 plantations, considering the criteria of gender, ethnic group, age range, education level, province and number of cultivated hectares. Among the results obtained, it should be noted that the age of the interviewees varies between 18 and 96 years, where 86.15% corresponds to the male gender and 13.85% to the female. 75.33% are of mestizo ethnicity, 10.39% montuvio and 3.9% of other ethnic groups. Ownership resides in men in 75.32%, in women in 11.69%, and in private companies or institutions in 12.99%. 61.05% of the producers indicated having the phytosanitary problem, but after evaluating the status of the plantations it was found that the disease occurred in 92.21%, therefore, 31.16% of the producers are unaware of the disease, which varies between 0 and 49% of incidence among the Ecuadorian provinces. Given that this phytosanitary problem is in most of the plantations, cultural management is recommended to reduce its dispersion.